MANAGING SUSTAINABLE TOURISM : THE ROLE OF LOCAL GOVERNMENTS IN OVERCOMING OVERTOURISM IN BALI - I Gede Druvananda Abhiseka; Putu Eva Ditayani Antari; Ni Kadek Rita Cahya Anggreni (Jurnal Komunikasi Hukum, 2025)
The phenomenon of overtourism in Bali Province has emerged as a critical challenge in the sustainable governance of the tourism sector. The continuously increasing number of tourists, without effective control measures, has caused numerous negative impacts on the environment, local culture, and community life. This research aims to analyze the legal authority and responsibilities of local governments in addressing over-tourism in Bali within the framework of national law, and this study also aims to evaluate how far the principles of good governance have been implemented in regional tourism policies. The researcher adopts a normative legal research method using statutory approaches, conceptual, and document-based approaches. The findings indicate that local governments possess legal legitimacy to formulate and implement policies rooted in local wisdom to mitigate over-tourism, as mandated by Law Number 23 of 2014 on Regional Government and other tourism-related regulations. The successful implementation of transparency, accountability, public participation, and law enforcement principles is essential to achieving sustainable tourism governance. However, several challenges remain, including weak coordination between central and local governments, lack of oversight, and short-term economic interests. Therefore, more responsive, collaborative, and datadriven legal policies are needed to address overtourism fairly and sustainably in Bali.